Development of a Digital Twin of The Technological Process of Consumable Pattern Casting Using Production Data - Doroshenko, V.S.; Kravchenko, V.P.; Tokova, O.V. (Control systems & computers, 2020)
The construction of a digital twin of a real physical object is described. It can be a virtual counterpart of a part, product, equipment, technological process, production sites, workshops or even factories. In fact, it is a set of mathematical models describing the state of an object and all its elements. The possibility of constructing a digital twin of an industrial facility is shown using the example of a consumable pattern casting workshop. Розглянуто дослідження по розробці систем комп’ютерного моніторингу параметрів технологічних процесів і станів об’єктів на прикладі цеху лиття по ЛГМ-процесу, а також методи їх раціонального вирішення на теоретичній основі сучасної прикладної математики. Рассмотрены исследования по разработке систем компьютерного мониторинга параметров технологических процессов и состояний объектов на примере цеха литья по ЛГМ-процесса, а также методы их рационального решения на теоретической основе современной прикладной математики.